Penerapan Pembelajaran Kooperatif Model GI dalam Meningkatkan Prestasi Belajar Tematik pada Siswa Kelas II Sekolah Dasar - Kasmawati Kasmawati (Universtas Negeri Makassar, 2022)
The aims of this study were: (a) To reveal the effect of the GI cooperative learning model on thematic learning outcomes. (b) Want to know how far the understanding and mastery of thematic subjects after the implementation of the GI cooperative learning model. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The results of the analysis found that student achievement increased from cycle I to cycle III, namely, cycle I (65.71%), cycle II (79.82%) cycle III (89.46%), and cycle I learning completeness reached ( 21.43%), cycle 2 (64.71%), and cycle 3 (83.33%) or are included in the complete category. The conclusion is that the application of the Group Investigation (GI) Model can increase student learning achievement so that this learning method can be used as an alternative to Thematic learning in elementary schools.